Pengaruh Harga, Pelayanan Dan Promosi Online Terhadap Keputusan Pembelian Pada Rumah Makan Gubuk Tiwul - Monitaria, Abi Melin; Baskoro, Ery (Jurnal Manajemen DIVERSIFIKASI, 2021)
The rapid number of food needs has made entrepreneurs in the culinary field in Indonesia compete to set up businesses because with this, entrepreneurs in the culinary field can become one of the supports for the existing economic structure in Indonesia. This has become one of the motivations for entrepreneurs in various regions without exception, one of them in the city of Metro Lampung to carry out business activities in the culinary field. One of the places to eat in the city of Metro is the Tiwul Hut Restaurant. As for the formulation of the problem in this study, namely "Is there a partial or simultaneous influence between price, service and online promotion on purchasing decisions at the Gubuk Tiwul restaurant". From these problems, the purpose of this study is to determine the effect of price, service and online promotion on purchasing decisions at the Tiwul Hut restaurant. The method in this research is quantitative. The technique used in data collection using a questionnaire. Then in data analysis using quantitative methods, the data collected is then processed and analyzed using SPSs. Based on data analysis using SSS, the conclusion in this study is that between price, service and online promotion, only services have a positive and significant effect on purchasing decisions at the Gubuk Tiwul restaurant, while simultaneously prices, services and online promotions have a positive and significant effect together. -same on the purchase decision at the Gubuk Tiwul restaurant. Keywords: Price, Service, Online Promotion, Purchase Decision